Construcción y evaluación de una estufa casera para el control de fusarium (Fusarium oxysporum) en semillas de amaranto (Amaranthus caudatus) - Jiménez Laverde, Byron Fernando (2017)
This research had as its purpose to promote the sustainable development of the amaranth production which a homemade stove served as a means of disinfection seed by solar radiation. Randomized design was used as methodology where was handled two studying factors, the temperature and the time same that managed with three repetitions and a witness with a factorial arrangement 2x3 1. The amaranth seeds (Amaranthus caudatus), were lay open to to three times of solar radiation exposure, during three, five and seven hours for three days, with two average temperatures of 40°C-60°C and 60°C- 80°C which by a data logger were measured. The treatment germination percentage 1 (T1), was the one that had the greatest significance whose percentage was 100 % valued at the rapid scale where the seeds were exposed to a temperature of 40 - 60°C for three, five and seven hours for three days too. The treatment 2 (T2), obtained an acceptable percentage of 70% valued at the slow scale, with seeds exposed to an average temperature of 60 - 80°C, during 3,5 and 7 hours. The pathogen incidence in the treatment 1 (T1), had an average of 67.6 %, with seeds exposed to 3.5 and 7 hours. The treatment II had a significant percentage of pathogen reduction 13%, but the germination was not given in its entirety. In comparison with the witnesses who presented a 100% of the pathogen presence. Obtaining as a result that the use of the stove as a disinfection means is feasible in the case of treatment 1 (T1), with average temperatures about 40 - 60°C, by 3.5 and 7 hours during 3 days of exposure.